PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 016 MARSAWA - Suparyono Suparyono (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is motivated by students' learning outcomes of Social Sciences which are still low. This study was conducted onstudents of class V SD Negeri 016 Marsawa. This study aims to improve student learning outcomes through cooperativelearning numbered heads together (NHT) type. From the data analysis of student learning outcomes before and afterapplying the NHT type cooperative learning model, students who completed only 16 people or 44.71%, while students whohave not completed as many as 19 people or 54.28% with classical completeness of 44%. After applying the NHT type ofcooperative learning model in cycle I, the number of students who completed increased to 25 people or 71.42%, while theunfinished number was 10 people or 28.57% with classical completeness of 70%. In the second cycle, the number of studentswho completed was 33 people or 94.2%, while the unfinished were 2 people or 5.71% with classical completeness of 94%.With this it can be concluded that by applying the numbered heads together (NHT) cooperative learning model can improvelearning outcomes of social sciences of students in class V SD Negeri 016 Marsawa